E-RECRUITMENT, SELEKSI, DAN PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN - Ratnasari, Sri Langgeng; Suryadinata, Puji Rahayu; Ariyati, Yannik (Jurnal Ecoment Global, 2022)
This study aims to determine and analyze the effect of e-recruitment on employee performance, to determine and analyze the effect of selection on employee performance, to determine and analyze the effect of employee placement on employee performance and to determine and analyze the effect of e-recruitment, selection, and employee placement. on employee performance. This study uses quantitative methods. The research population is 50 employees recruited using e-recruitment. The sampling technique used a saturated sample. The results showed that E-Recruitment had a positive and significant effect on the performance of PT. Cakra Mandiri Perkasa, while the selection has a positive and significant effect on the performance of employees of PT. Cakra Mandiri Perkasa and Employee Placement have a positive and significant effect on the performance of PT. Cakra Mandiri Perkasa. The influence of E-Recruitment, Selection and Placement of Employees simultaneously has a significant effect on Employee Performance at PT. Cakra Mandiri Perkasa.